Phase balancing in Nd:Yag laser welding of preheated UNS S32750 superduplex steel - Crespo, G. S. [UNESP]; Ventrella, V. A. [UNESP] (My University, 2023)
Two UNS S32750 superduplex steel sheets were heated in an oven and subsequently subjected to a Nd:YAG laser welding process in pulsed mode. The first sheet was welded after it was completely cooled in the air (default condition: CP), while the second sheet was welded immediately after its removal from the oven (heated condition: CA). The welding processes in both conditions were carried out in an autogenous manner, at a frequency of 15 Hz, welding speed of 1.7 mm/s, temporal width of 5 ms, peak energy of 2 kW, and without the use of protection. After the welding process, the weld beads were sectioned in their transverse directions, embedded in hot curing Bakelite and subjected to the standard metallographic preparation process, with revelation of the metallographic structure of the weld metals by using Behara II reagent. Macrographs and micrographs were performed under a common optical microscope and, under a scanning electron microscope (SEM), of the weld metals of both conditions, which were used for geometric evaluation (width and depth) of the weld metals and evaluation of the balance volumetric analysis of austenite/ferrite phases, post-welding process. Energy-dispersive spectroscopy (EDS) analyses were also performed on the weld metals under the two conditions, to evaluate the variation, in relation to the base metal, of the three alloying elements (Cr, Ni, and Mo) present in greater amounts. In the geometric analyses, CA weld metal was approximately 41.8% deeper and 11.2% wider than CP weld metal, indicating a strong influence of sheet heating on laser beam penetration during the welding process. In volumetric phase balancing, the heating of the plate reflected an increase in the average percentage of austenite in the weld metal, from 10.9% to 46.7%, causing a reduction in the austenite phase imbalance, from 39.1% to 3.3%. Finally, in relation to the alloying elements in the weld metals, the CA sample presented a higher Cr value, while the CP sample presented higher Mo and Ni values when compared to each other. In relation to the base metal, both weld metals showed higher percentages for the three alloying elements, in line with the expected behavior for each condition, according to the phase balance data obtained.
Keywords: Heating; Laser; Nd:YAG; UNS S32750